(untitled) (Journal of Hama University, 2026)
ABSTRACT The current research aimed to determine the relationship between emotional intelligence and burnout on a multidisciplinary sample of nurses working at Tishreen University Hospital and to identify relevant variables. Detect the differences between the average scores of sample members on the emotional intelligence scale and its relationship to burnout according to the variables (gender, specialty). The research adopted the descriptive approach, and the research community included all nurses working at Tishreen University Hospital, numbering (1355), where (270) of the scale were distributed to the nurses working at Tishreen University Hospital. The results showed that the arithmetic mean of the dimension of perceiving and managing emotions was greater (3.71) and a relative weight of (92.85) than the dimension of self-motivation and social skills (3.67) and a relative weight of (91.87). This indicates that the degree of emotional intelligence among nurses working at Tishreen University Hospital in both dimensions was at a high level. In the three dimensions of burnout, it was found that nurses have low burnout and a low level as a result of their possession of emotional intelligence, through which they are able to skillfully adapt to work pressures. There is also a statistically significant relationship at a significance level of (a = 0.05) between emotional intelligence and burnout among nurses working at Tishreen University Hospital. It was also found that there are no statistically significant differences at a significance level of 0.05 between the average scores of the sample members on the total score of the scale of dimensions of emotional intelligence and burnout among nurses working at Tishreen University Hospital according to the variables (gender, specialty)..